1966
DOI: 10.1128/jb.91.2.609-616.1966
|View full text |Cite
|
Sign up to set email alerts
|

Influence of Lipid Components of Mycoplasma laidlawii Membranes on Osmotic Fragility of Cells

Abstract: Influence of lipid components of Mycoplasma laidlawii membranes on osmotic fragility of cells. J. Bacteriol. 91:609-616. 1966.-Lipid composition of Mycoplasma laidlawii membranes could be significantly changed by variations in the growth medium. The effect of these changes on the osmotic fragility of the cells was studied. Cholesterol, incorporated into the membrane from the growth medium, had no significant effect on osmotic fragility. Carotenoids, synthesized by the cells from acetate, were likewise without … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

2
21
1

Year Published

1972
1972
1993
1993

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 105 publications
(24 citation statements)
references
References 28 publications
2
21
1
Order By: Relevance
“…These results could be explained if cholesterol were to alter the spacing of polar head groups in the bilayer so as to allow solvent to enter the hydrocarbon core. The association of cholesterol with phospholipid acyl side chains is well established (14)(15)(16)(17)(18). It is generally believed, and our fluorescence data are in complete accord, that sterol increases the mobility of rigid side chains, while reducing the mobility of liquid ones (19)(20)(21)(22)(23)(24).…”
Section: Discussionmentioning
confidence: 99%
“…These results could be explained if cholesterol were to alter the spacing of polar head groups in the bilayer so as to allow solvent to enter the hydrocarbon core. The association of cholesterol with phospholipid acyl side chains is well established (14)(15)(16)(17)(18). It is generally believed, and our fluorescence data are in complete accord, that sterol increases the mobility of rigid side chains, while reducing the mobility of liquid ones (19)(20)(21)(22)(23)(24).…”
Section: Discussionmentioning
confidence: 99%
“…Increasing unsaturation of long-chain fatty acids has been shown to increase permeability in artificial membranes (2). Razin et al (8) found that oleic acid and other unsaturated longchain fatty acids added to the medium (and found to be incorporated into the membrane) increased the resistance of Mycoplasma laidlawii to osmotic lysis. Others have shown that the degree of unsaturation of the fatty acids of erythrocytes correlated with the resistance of the red cells to hemolysis (10).…”
Section: Discussionmentioning
confidence: 99%
“…(v) The ability to alter the fatty acid composition of membrane polar lipids in a predictable manner by the alkane carbon source employed provides an excellent model system for an investigation of membrane structure-function relationships. Mycoplasma laidlawii B polar lipids respond with predictable pattems to the incorporation of a wide range of added fatty acids (9,20). The microorganism M. cerificans offers an excellent model system for the investigation of structure-function relationships in biological membranes.…”
Section: Discussionmentioning
confidence: 99%